Macroalgal Composition Determines the Structure of Benthic Assemblages Colonizing Fragmented Habitats. - Miguel G Matias (PLoS ONE, 2015)
Understanding the consequences of fragmentation of coastal habitats is an important topic of discussion in marine ecology. Research on the effects of fragmentation has revealed complex and context-dependent biotic responses, which prevent generalizations across different habitats or study organisms. The effects of fragmentation in marine environments have been rarely investigated across heterogeneous habitats, since most studies have focused on a single type of habitat or patch. In this study, we assessed the effects of different levels of fragmentation (i.e. decreasing size of patches without overall habitat loss). We measured these effects using assemblages of macro-invertebrates colonizing representative morphological groups of intertidal macroalgae (e.g. encrusting, turf and canopy-forming algae). For this purpose, we constructed artificial assemblages with different combinations of morphological groups and increasing levels of fragmentation by manipulating the amount of bare rock or the spatial arrangement of different species in mixed assemblages. In general, our results showed that 1) fragmentation did not significantly affect the assemblages of macroinvertebrates; 2) at greater levels of fragmentation, there were greater numbers of species in mixed algal assemblages, suggesting that higher habitat complexity promotes species colonization. Our results suggest that predicting the consequences of fragmentation in heterogeneous habitats is dependent on the type and diversity of morphological groups making up those habitats.